Mengukur Tingkat Penerimaan dan Kepuasan Siswa terhadap Pembelajaran PAI dengan Model Hannafin dan Peck - Nugraha, Mulyawan Safwandy; Bakhtiar, Yusup Hamdani; Dedih, Ujang (Lembaga Yasin AlSys, 2024)
In the era of the industrial revolution 4.0, everything is digital. Children are no strangers to gadgets. So parents and educators must try extra hard so that gadgets can become a medium for learning and learning for children. Educators must be smart and creative in choosing learning models or methods that will be applied to students at school, as well as in Islamic Religious Education learning. Teachers are required to be creative and innovative in developing learning models or methods. The approach used in this study is a qualitative approach that aims to understand the phenomena experienced by the research subjects. The Hannafin and Peck model is a teaching design model consisting of three phases, namely the needs analysis phase, the design phase, and the development and implementation phase. Advantages: This model can produce learning products because it is product-oriented. The model performs assessment and iteration at each phase. Identifying gaps in the first stage can help the analysis stage. The downside: This model can only be used for certain (uncommon) problems. More inclined to media creation.